An epidemic of acute postinfectious glomerulonephritis in Armenia. Issue 4 (1st October 1997) - Sarkissian, Ashot; Papazian, Marina; Azatian, Gayane; Arikiants, Nina; Babloyan, Ara; Leumann, Ernst
Abstract : AIM: To evaluate the presentation and course of acute postinfectious glomerulonephritis (APGN), which has increased dramatically in Armenia after serious deterioration in the living conditions. STUDY DESIGN: Observational study, based on case notes, of a large homogeneous group of patients hospitalised for APGN at one centre over a five year period (1992–6). PATIENTS: 474 patients aged <16 years with a diagnosis of APGN. RESULTS: The annual number of patients increased tenfold from 19 (average 1992/3) to 196 in 1995. Sixty two per cent were in the age group 4–9 years and 65% were boys. Upper respiratory infections, scarlet fever, and skin infections preceded APGN in 51%, 23%, and 13%, respectively. All patients had haematuria (93% gross), 84% had oedema, and 72% had hypertension. C3 was initially decreased in 95% of the patients examined. Renal function was impaired (serum creatinine > 100 μmol/l) in 29%. Four patients with renal failure had crescentic glomerulonephritis at biopsy; of these, three required temporary haemodialysis. Main extrarenal complications were heart failure (10%) and convulsions (3%). One patient died and five (3%) did not recover completely. CONCLUSIONS: APGN in children is associated with considerable initial morbidity, and long term outcome is not uniformly benign. Outbreaks of APGN may occur anytime in countries such as Armenia that are suffering from a sudden decline in socioeconomic conditions.